2019
DOI: 10.3390/rs11030349
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Approach for Soil Moisture Estimation in Gully Fields of the Loess Plateau Using Sentinel-1A Radar Images

Abstract: As an essential ecological parameter, soil moisture is important for understanding the water exchange between the land surface and the atmosphere, especially in the Loess Plateau (China). Although Synthetic Aperture Radar (SAR) images can be used for soil moisture retrieval, it is still a challenge to mitigate the impacts of complex terrain over hilly areas. Therefore, the objective of this paper is to propose an improved approach for soil moisture estimation in gully fields based on the joint use of the Advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The physically-based IEM surface scattering model [36], of which various versions have widely been used (e.g., [1][2][3]5,20,49,[59][60][61][62][63][64]), simulates the σ 0 of bare land surfaces as a function of the land surface's geometric and dielectric properties. For more background on the IEM model, readers are referred to Ulaby et al [6].…”
Section: Impact On Soil Moisture Retrieval Accuracymentioning
confidence: 99%
“…The physically-based IEM surface scattering model [36], of which various versions have widely been used (e.g., [1][2][3]5,20,49,[59][60][61][62][63][64]), simulates the σ 0 of bare land surfaces as a function of the land surface's geometric and dielectric properties. For more background on the IEM model, readers are referred to Ulaby et al [6].…”
Section: Impact On Soil Moisture Retrieval Accuracymentioning
confidence: 99%
“…Although Sentinel-1 images have rarely been used as predictor variables for mapping STN, previous studies using these images to monitor vegetation demonstrated the ability of SAR data to capture vegetation information, which can be further applied to map STN because of the relationships in the soil-vegetation system. For example, Guo et al [67] found that the combination of Sentinel-1 and Sentinel-2 obtained the best above-ground biomass monitoring results while Navarro et al [68] used Sentinel-1 to obtain satisfactory soil moisture inversion results on the Loess Plateau of China.…”
Section: Importance Of Predictor Variablesmentioning
confidence: 99%
“…Soil moisture (SM) is an important state variable that significantly affects the water cycle, ecosystem, and energy exchange between the land and the atmosphere. SM information is important in different fields, such as agriculture, meteorology, hydrology, weather, and evapotranspiration forecasting [1][2][3][4][5][6][7]. In recent decades, in the large-scale domain, the development of remote sensing technology has provided more opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, synthetic aperture radar (SAR) has been the primary active microwave remote sensing means of monitoring SM [6,21]. However, in vegetation-covered areas, the signal includes direct scattering from plant cover and attenuated backscatter from the ground.…”
Section: Introductionmentioning
confidence: 99%